SEXUALITY AND SEXUAL EDUCATION: PRIORITIES IN THE TRAINING OF ADOLESCENTS - Mateus Calgarotto, Vitor (Revista Gênero e Interdisciplinaridade, 2023)
If we analyze the concept of Sexual Education in recent years, we will observe that discussions have become increasingly complex, with a much greater focus on mental health and autonomy relationships regarding safe sex, gender identity and others. The search for the sexual health of adolescents has taken up a large space among research in the area of education, as a result of the difficulties encountered by educational agents regarding this topic. In this way, the school becomes a privileged space to address issues related to sexuality, when we know that other entities in society are omitted or perpetuate prejudices and stigmas. Therefore, a focus on public policies and the training of education professionals is necessary, mainly in relation to the methodology for working on the subject; also identifying the obstacles that make the teacher stop working on such content. Thus, this study presents a bibliographical review regarding the history of sexual education in Brazil, the right to sexuality and its violations, health promotion in adolescence and, especially, the role of Biological Sciences teachers, focused on comprehensive training of adolescents from a critical perspective.